O uchodźcach z Grecji (i nie tylko) na lekcji we współczesnej szkole – Nowe życie. Jak Polacy pomogli uchodźcom z Grecji Dionisiosa Sturisa - Ochwat, Magdalena (Postscriptum Polonistyczne, 2020)
The article refers to the turn of the 1940s and 1950s of the 20th century, when the Greek refugees, the victims of the civil war, arrived in Poland. There were approximately 14 thousands of them. The article author refers to the concept of literature that delights with the good and the school that shapes minds and civic attitudes, which is essential in the contemporary world, marked with migration crises.